2002
DOI: 10.1046/j.1365-2222.2002.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Coding single nucleotide polymorphism in the high‐affinity immunoglobulin E receptor b chain (Fc"RI‐b) gene is associated with immunoglobulin E receptor‐mediated histamine release from basophils

Abstract: This study supports a role for the FcepsilonRI-beta gene in the expression of high affinity IgE receptor-mediated histamine release from basophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Aggregation of Fc⑀RI by the interaction of bound IgE with multivalent antigens induces the release of histamine, leukotrienes, and inflammatory cytokines, resulting in the recruitment and activation of circulating leukocytes leading to allergic inflammation (2). Polymorphisms in the Fc⑀RI␤ have been linked to atopy, asthma, and allergy (3)(4)(5). However, studies on the role of these polymorphisms in Fc⑀RI expression and function have not yielded an understanding of their effects on mast cell physiology (6,7).…”
mentioning
confidence: 99%
“…Aggregation of Fc⑀RI by the interaction of bound IgE with multivalent antigens induces the release of histamine, leukotrienes, and inflammatory cytokines, resulting in the recruitment and activation of circulating leukocytes leading to allergic inflammation (2). Polymorphisms in the Fc⑀RI␤ have been linked to atopy, asthma, and allergy (3)(4)(5). However, studies on the role of these polymorphisms in Fc⑀RI expression and function have not yielded an understanding of their effects on mast cell physiology (6,7).…”
mentioning
confidence: 99%
“…While the genes for the alpha and gamma subunits are both located on human and mouse chromosome 1 (18), the beta gene is located on 11q13 and spans about 10 kb and contains 7 exons (19). Although polymorphisms of the FCER1B gene has been reported to be associated with atopy, total serum IgE level, bronchial hyperresponsiveness, asthma, and the basophilic histamine-releasing activity of asthmatic patients (8-11, 20), no previous study has been made of the association between FCER1B gene polymorphisms and urticaria/angioedema. This study, therefore, is the first to investigate whether no significant association is found between the FCER1B gene polymorphism with the AIU phenotype in a Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies revealed that a locus in the long arm (q) of chromosome 11 at bands 12-13 (11q12-13), which contains the FcεRIβ gene, is linked with allergy [10,14]. Additional analysis revealed the identified polymorphisms as associated with atopy, asthma, allergic rhinitis, bronchial hyperesponsiveness, atopic dermatitis, total serum IgE levels, and histamine release from basophils in various populations [9,[11][12][13]. The described single nucleotide polymorphisms (SNPs) in In contrast, the YFY mutant showed enhanced cytokine synthesis and secretion of IL-6, IL-13, and TNF-α (Fig.…”
Section: Fcεriβ Polymorphisms and Link To Allergic Diseasementioning
confidence: 99%
“…Kinet and colleagues [7,8], demonstrated that the β subunit serves a key role in amplifying the intracellular signaling that is important for mast cell release of a variety of preformed allergic mediators. This key role in amplifying responses, and thus controlling the sensitivity of a mast cell, has led to the hypothesis that polymorphisms in the β subunit shown be linked to atopy, allergy, and asthma [9][10][11][12][13][14], might affect the signaling ability of the β subunit and thus FcεRI. However, several studies have explored this possibility by reconstituting cellular expression of the polymorphic β subunit without achieving any measurable changes in cellular function [15,16].…”
mentioning
confidence: 99%